2015
DOI: 10.1007/s12289-015-1273-4
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and numerical investigation of the effect of macro-textured tool surfaces in hot stamping

Abstract: This paper presents a method of increasing drawability of materials in hot stamping processes using forming tools with macro-scale textures on the tool surfaces. Firstly, a series of tool texture designs and orientations were presented and a test programme was designed for the experimental investigation. Top-hat shape drawing experiments in cold and hot stamping conditions were conducted to evaluate the effect of macro-scale tool surface textures on the material drawing. Texture directional and texture feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The clearance between the die and punch was 0.1 times of test-piece thickness. Macro-textures were machined on blankholder surfaces in the radial direction to avoid the constraint effect if the macro-textures are not parallel with material flow direction [14], using CNC milling and related to function, and can be divided into two features: groove and surface.…”
Section: Experimental Set-up and Tool Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The clearance between the die and punch was 0.1 times of test-piece thickness. Macro-textures were machined on blankholder surfaces in the radial direction to avoid the constraint effect if the macro-textures are not parallel with material flow direction [14], using CNC milling and related to function, and can be divided into two features: groove and surface.…”
Section: Experimental Set-up and Tool Preparationmentioning
confidence: 99%
“…Costa and Hutchings [12][13] found that friction was significantly reduced through the use of patterned tool surfaces in strip drawing processes, where these grooves were believed to act as lubricant reservoirs to enhance the lubrication effect. Zheng et al [14] investigated hot stamping processes of aluminium alloys using macro-textured tools, which enabled the blank temperature at the flange area to be relatively preserved, with a significant increase in draw-ability being observed due to a more uniform temperature distribution throughout the blank. However, for components with complex geometry, macrotextures may cause wrinkling in the flange area due to the absence of blank-holding contact in the region of a texture hollow.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the elastic-plastic dominated cold stamping process, typical characteristics for elevated temperature forming are: (1) microstructure evolution is complex with the coupled effects of dislocation, recovery and dynamic recrystallization in some particular conditions on the hot flow and post proper-ties [8]; (2) strain rate sensitive viscoplastic deformation becomes dominant [9]. The uniformity of deformation is highly dependent on the forming speed and temperature [10]. Therefore, the design of process and selection of process parameters for forming a complex-shaped component are challenging, requiring the aid of robust finite element (FE) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The nonisothermal feature of hot stamping processes due to the heat transfer between the hot work-piece and the cold dies results in non-uniform deformations, which affect hot formability significantly. This issue can be alleviated with the use of macro-textured tool surfaces, such as the one introducted by Zheng et al [9]. The use of textured tools significantly reduces the contact area and heat transfer compared to traditional flat tool designs.…”
Section: Introductionmentioning
confidence: 99%